2019
DOI: 10.3389/fgene.2019.00001
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Next Generation Sequencing Revealed a Novel Homozygous Loss-of-Function Mutation in ILDR1 Gene Causes Autosomal Recessive Nonsyndromic Sensorineural Hearing Loss in a Chinese Family

Abstract: Hereditary hearing impairment is one of the major and common birth defects in Chinese population. Non-syndromic sensorineural hearing loss (NSHL) is the most common types of hereditary hearing impairment. Genotypically and phenotypically NSHL is extremely heterogenous and follow either autosomal dominant or autosomal recessive or X-linked mode of inheritance. Presently, 127 genes have been identified to be associated with both syndromic and (NSHL). Here, we studied a Chinese family with moderate and profound h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
123
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(128 citation statements)
references
References 24 publications
5
123
0
Order By: Relevance
“…K63-linked polyubiquitin chains play an essential role in signal amplification processes for various cellular stress responses, including DNA repair and nuclear factor κB activation 84 . Its role in signaling has recently expanded to translation as it was reported that K63-linked ubiquitylation of ribosomal proteins activates multiple downstream quality control pathways, and the modification by Hel2 provides a platform for the interaction of ribosomes with other E3s or regulatory components 21,83,85 . Combined with the prevalence of damaging adducts in mRNA in the absence of Xrn1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…K63-linked polyubiquitin chains play an essential role in signal amplification processes for various cellular stress responses, including DNA repair and nuclear factor κB activation 84 . Its role in signaling has recently expanded to translation as it was reported that K63-linked ubiquitylation of ribosomal proteins activates multiple downstream quality control pathways, and the modification by Hel2 provides a platform for the interaction of ribosomes with other E3s or regulatory components 21,83,85 . Combined with the prevalence of damaging adducts in mRNA in the absence of Xrn1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4). Similarly, one of the most widely applied plasticising compound (bisphenol A) has been associated with altered zebrafish larval locomotion 51 . However, in natural systems, it is conceivable that behavioural effects are ultimately dependent on developmental stage and the result of a combination of a particle and plastic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted next-generation sequencing (TGS) analyses with 256 disease-causing genes panel were performed on an M101 DNA sample, according to the manual from Illumina as previously described (Zhang et al, 2016;Fu et al, 2017Soens et al, 2017;An et al, 2019). Library construction, TGS, bioinformatic computational framework and data analysis were executed according to the manufacturer's protocols (Koenekoop et al, 2012;Soens et al, 2016;Fu et al, 2017;Adams and Eng, 2018;An et al, 2019). Ninety-six percent of the targeted regions have coverage >20× and 91.1% of the targeted regions have coverage >40×.…”
Section: Targeted Ngs Quality Control and Bioinformatics Analysismentioning
confidence: 99%
“…UGENE was used to perform the multiple sequence alignment using the MUSCLE alignment algorithm (Soens et al, 2016). The comprehensive and method of variant interpretation in detail has been described in An's study (An et al, 2019).…”
Section: Targeted Ngs Quality Control and Bioinformatics Analysismentioning
confidence: 99%